Control of Root Maggots in Swede Turnips in Newfoundland with Heptachlor and Aldrin and the Effect on Parasites and Overwintering Pupae - Morris, Ray F. (Journal of Economic Entomology, 1960)
Furrow applications of granulated heptachlor at 2,3 and 4 pounds of toxicant per acre gave an average control of 78%. 88% and 89%, respectively, of root maggots in swede turnips in a 3-year period; granulated aldrin at 2,3,4 and 5 pounds 63%, 71%, 76% and 79%. Ninety-one to 100% of the roots in the heptachlor-treated plots and 80% to 98% of those treated with aldrin were marketable; in untreated checks, 29% to 40%. Numbers of overwintering puparia provided a reliable index to the effectiveness of the chemicals. A highly significant correlation was noted between the number of pup aria recovered and the infestation index. Both chemicals, particularly at the higher rates of application evidently caused high mortality in overwintering pupae. The insecticides eliminated the staphylinid parasite, Aleochara bilineata Gyll., and reduced parasitism of the pupae by the cynipid, Trybliographa rapae (West w.), from 9% to less than 2%.